O uso de línguas eletrônicas voltamétricas para a detecção de adulteração em alimentos - Ichikura, Júlia Tiemy (Universidade Federal de São Carlos, 2024)
THE USE OF VOLTAMMETRIC ELECTRONIC TONGUES FOR DETECTING ADULTERATION IN FOOD is briefly revised through three examples reported in the literature on the subject. Specifically, these examples involve the use of this advantageous tool in adulteration analyses, the electronic tongue, to identify adulterants in samples of honey, wine, and coffee. Electronic tongues are systems with electrochemical sensors associated with software known as intelligent sensory algorithms (chemometric methods). The three works were chosen due to two main reasons. Firstly, they demonstrate how advantageous the voltammetric electronic tongues are compared to other types of analytical techniques previously reported in the literature, in particular their speed, accuracy, and sensitivity. The other reason arises from the fact that the foods used in their respective sample sets are among the most adulterated and defrauded in the world in recent years. Thus, this study presents methodologies developed using electronic tongues, based on voltammetric techniques of detection (more specifically, Square-Wave Voltammetry and Cyclic Voltammetry) and chemometric methods, to identify adulterations in samples of some human consumption products.
The use of voltammetric electronic tongues for detecting adulteration in food
Keywords: Adulteração de alimentos; Química eletroanalítica; Língua eletrônica; Mel; Vinho; Café; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ELETROANALITICA